Societal e-readiness for e-governance adaptability in Pakistan - Mukaram Ali Khan; Sobia Khurram; Syed Sohaib Zubair (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The idea of e-governance is being appreciated and worked upon at various levels, however,this research focuses on the need of various workingsbefore e-governance mechanisms can actually be made operational. The literature suggests that any policy or reform that does not cater the local context and fulfill all pre-requisites is likely to faceserious hurdles and therefore might not reap desired results. The prime focus of this research is to test the societal e-readiness in connection with the idea of e-governance adaptability in the context of Pakistan. Recently, in Pakistan, several initiatives have been taken by government in order to shift towards this IT based governance structure from the traditional mode of governance. Based on the data collected from 312 university students and professionals, the developed model was tested using covariance based structural equation modeling (SEM) and the findings reveal that basic operational knowledge, networked society and availability of infrastructure respectively, are important facilitators that strengthen E-Governance adaptability. Apart from this inferential analysis, descriptive statistics were also used to identify various hurdles that people perceive regarding e-governance adaptability and it was found that resistance to change and lack of awareness are the biggest hurdles that people in Pakistan believe in the context of e-governance adaptability. Not just at the operational or practical level, the study also adds to the literature on new public governance theories
Keywords: 330; e-governance; societal e-readiness; availability of infrastructure; networked society; basic operational knowledge